Are Tax Retention Rate, Investment Opportunity Set, and Growth Opportunities Important in Determining the Quality of Corporate Earnings? - Septi Hastareni; Riska Alfriani; Sekar Mayangsari (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2025)
Research Background: When a company has good profit growth potential, the need for robust tax planning becomes even greater. Proper tax planning not only maximizes profits but also enhances the quality of reported profits. Tax planning and profit management share a common goal—achieving profit targets by strategically managing the company's profit figures. Introduction/ Objectives: This study adopts a causal-associative approach to examine the influence of the Tax Retention Rate, Investment Opportunity Set (IOS), and Growth Opportunity on earnings quality in property and real estate companies listed on the Indonesia Stock Exchange (IDX). Methods: The research employs quantitative secondary data. The population comprises all property and real estate companies. Using census sampling, 17 companies were selected over a 5-year period, resulting in 85 observations. The analysis utilizes Structural Equation Modeling (SEM) with SmartPLS. Results: Findings reveal that Growth Opportunity, Moderating Effects 2 and 3, and Tax Retention Rate significantly impact earnings quality, while GCG, IOS, and Moderating Effect 1 show no influence. Moderating Effect 1 weakens, whereas Moderating Effects 2 and 3 enhance the relationship between the independent and dependent variables. Conclusions: The implications of these findings are clear: effective investment planning and efficient tax management are crucial for improving earnings quality. Companies should focus on maximizing growth opportunities, managing tax retention rates carefully, and fostering the right moderating conditions to improve the accuracy and transparency of their earnings reports.